2019
DOI: 10.1080/09638288.2018.1534006
|View full text |Cite
|
Sign up to set email alerts
|

Expectations management; employer perspectives on opportunities for improved employment of persons with mental disabilities in Kenya*

Abstract: Purpose: In Kenya, the employment rate for persons with disabilities is about 1% compared to 73.8% for the general population, and the situation is even worse for persons with mental disabilities. Persons with mental disabilities are often regarded as "mad", and stand little or no chance of employment. We undertook an exploratory study with employers and potential employers to understand factors that hinder or facilitate their employment and to gain insight into employers' perceptions of mental disability. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Lastly, social exclusion also occurred among employers and co-workers, making them give up work in formal settings on account of anticipated stigma. These findings are corroborated by studies in high-income countries, but what makes our study different is the absence of mechanisms in our setting to ensure reasonable accommodation for persons with mental disabilities (30, 4143). The absence of these mechanisms also highlights the heightened effect of these experiences on work opportunities.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Lastly, social exclusion also occurred among employers and co-workers, making them give up work in formal settings on account of anticipated stigma. These findings are corroborated by studies in high-income countries, but what makes our study different is the absence of mechanisms in our setting to ensure reasonable accommodation for persons with mental disabilities (30, 4143). The absence of these mechanisms also highlights the heightened effect of these experiences on work opportunities.…”
Section: Discussionsupporting
confidence: 84%
“…Few studies have explored the employment experience of persons with mental disabilities in Kenya or looked into the interplay between societal and individual factors from the perspective of persons with mental disabilities. We have explored the perspectives of other stakeholders such as employers, mental health-care providers, workers in disabled persons/mental health organizations in separate articles (30, 31). This study aims to highlight not only the individual and environmental barriers to employment experienced by persons with mental disabilities in Kenya but also how they, as individuals, supported by their environment, manage against all the odds to find employment.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread social stigma that cuts across all social strata in this study is another barrier. The fear and lack of information among employers reinforces the stigma and limits their employment of persons with mental disorders [44]. The stigma borne by the family and other individuals deprives persons with mental disorders of the health care they deserve; and, sadly, the actions of certain healthcare workers may also stigmatize them further.…”
Section: Missingmentioning
confidence: 99%
“…Unemployment is a barrier to the recovery and well-being of people living with disabilities in Kenya. As it stands only 1% of Kenyan adults with a disability are employed, compared to approximately 74% of Kenyan adults within the country´s general population, with women experiencing higher levels of systemic exclusion in work and employment than men [ 7 , 8 ]. This is extremely low compared to other geographical areas [ 9 ], however it is not due to a lack of interest in work amongst PWPD.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the stigma and misconceptions prevalent in society also extends to employers. It has been found that employers are often unwilling to employ PWPD for reasons such as fear for safety, concern that workplace productivity will decrease and beliefs that PWPD are unable to do basic job tasks population [ 8 ]. Consequentially few PWPD have the confidence to disclose their mental health status with their employers, meaning that they are unable to access accommodations and equity benefits that might contribute to a more conducive working environment.…”
Section: Introductionmentioning
confidence: 99%